The Southern Top of the World: The First Peopling of Patagonia and Tierra del Fuego and the Cultural Endurance of the Fuegian Sea-Nomads - Piana, Ernesto Luis (2009)
The Southern Top of the World: The First Peopling of Patagonia and Tierra del Fuego and the Cultural Endurance of the Fuegian Sea-Nomads Ernesto Luis Piana and Luis Abel Orquera Ernesto Luis Piana, Centro Austral de Investigaciones Científicas (CONICET), Bernardo Houssay 200, 9410 Ushuaia, ArgentinaLuis Abel Orquera, Asociación de Investigaciones Antropológicas, Bartolomé Mitre 1131, 7° "G", 1036 Buenos Aires, Argentina Patagonia and Tierra del Fuego include contrasting environments and populations. Both were settled more than 10,000 years ago, although the coastal resources were not intensively exploited until four millennia later. The littoral resource exploitation had very different characteristics on the Atlantic compared to the Magellan-Fuegian coasts. Generalized strategies were maintained in the former, while in the latter the inhabitants developed a specialization—they became intensively dependent on the littoral and marine resources and designed special technological means for their procurement and processing, including navigation capability. This process began some 6,400 radiocarbon years ago and these sea-nomads colonized the southernmost archipelago from the Beagle Channel down to Cape Horn. After synthesizing the settling of Patagonia, this paper focuses on the process of colonization and cultural endurance of the sea-nomads until the time of European contact.